Polymers of Z α1-antitrypsin are secreted in cell models of disease. Issue 3 (4th February 2016) - Fra, Annamaria; Cosmi, Francesca; Ordoñez, Adriana; Berardelli, Romina; Perez, Juan; Guadagno, Noemi A.; Corda, Luciano; Marciniak, Stefan J.; Lomas, David A.; Miranda, Elena
The α1 -antitrypsin (α1 -AT) is a 52 kDa glycoprotein that is predominantly synthesised in the liver and secreted into the circulation, where it protects the lungs from the enzyme neutrophil elastase. α1 -AT deficiency (α1 -ATD) is caused by mutations in the α1 -AT gene, with most cases resulting from homozygous inheritance of the Z allele (Glu342Lys). This leads to low levels of circulating α1 -AT, uncontrolled elastase activity and emphysema [1]. The Z mutation destabilises the native α1 -AT and causes the formation of aberrant polymers that accumulate within the endoplasmic reticulum (ER) of hepatocytes, giving rise to inclusion bodies that are the main histological feature of α1 -ATD [2]. Extracellular polymers have been found in lung lavage, the skin of an individual with panniculitis and the kidney of an individual with vasculitis [1], and are also present in the circulation of all individuals homo- or heterozygous for the Z allele [3]. Circulating polymers originate in the liver, since they became undetectable in the plasma of an individual 4 days after liver transplantation [3], but it is unknown whether polymers can be secreted from hepatocytes or can form in the extracellular environment from secreted monomeric Z α1 -AT. Extracellular polymers are chemotactic and stimulatory for human neutrophils [4] and may contribute to inflammatory neutrophil infiltration in the lungs, kidney and skin. It is important to understand where these polymers form in order to design effective therapies for emphysema and other pathological manifestations of α1 -ATD. Here we investigated the origin of extracellular polymers by exploiting our cellular models of α1 -ATD and conformer-specific and functional monoclonal antibodies (mAb) against Z α1 -AT [5–8]. Pathological polymers of Z alpha1-AT can be secreted from cells through the canonical secretory pathway http://ow.ly/WHxZh